Diet of Leopardus colocolo (Carnivora: Felidae) in the Reserva Nacional de Junín, Junín, Peru - Fajardo, Ursula (2014)
This study characterized the diet of Leopardus colocolo from the surroundings of Junín lake, in the center of Peru, from prey remnants found within 43 scats. Origin of predator scats was determined from mitochondrial DNA from intestinal epithelial cells existing on the surface of the scats, using as a marker the control region. The prey remnants were identified using specialized literature and comparison with a voucher collection, identifying a total of 14 food items belong to mammals of Cricetidae (6), Chinchillidae (1) and Caviidae (1) families, birds of Anatidae (3) and Rallidae (2) families and one group of unidentified birds. The rodents were the main component of the diet of L. colocolo, in frequency and biomass, followed by birds. Among the food items consumed, the small cricetine rodent Calomys sp. was the most frequent; however, the greatest relative biomass contribution was provided by the medium rodent Cavia tschudii. The niche breadth obtained was low (Bsta= 0.17), indicating a specialized diet. Our results confirm that, as with most neotropical small felids, L. colocolo is a predator specialized in capturing vertebrates, mainly small mammals. No seasonal variation was recorded in the diet and the analysis of the age class of the cricetine rodents showed that the adults were the most consumed. It is inferred that L. colocolo have diurnal and nocturnal activity patterns.